“Determinación de parásitos gastrointestinales en caninos menores de un año de edad en la parroquia Clemente Baquerizo de la Ciudad de Babahoyo”. - Euvin Carranza, Georgina Rocio (2023)
The objective of this investigative work is to determine the presence of gastrointestinal parasites in canines under one year of age in the Clemente Baquerizo parish of the city of Babahoyo, before and now the family has incorporated pets into its members that are considered as part of their She and the canines are a fundamental part of her daily environment, the care used in the upbringing of this species, such as food, health and well-being, all with the aim of ensuring that your pet leads a dignified life and is not means of transmission of diseases to the other members of the family, 100 canines under one year of age were taken as a sample, through the fecal sample directly from the rectum of the canine with the help of a swab and by simple flotation an adequate amount by placing sodium chloride with feces in a test tube, once the sample is taken, both tests will be carried out on the slide covered with a cover sheet, to be taken under the microscope and determine what type of parasites will be found in each animal, obtaining as a result that the gastrointestinal parasites identified are Toxocara Canis, Ancylostomas, Coccidia, Dipilidium and that those found with a high percentage of prevalence in the samples were Toxocara canis and Ancylostoma caninum each with 17% and 13%, Toxocara Canis, Dipilidium Coccidia with 1%, Ancylostomas, Coccidia with 1%, Ancylostomas, Toxocara Canis with 5%, Toxocara Canis, Coccidia with 2%, Ancylostomas, Toxocara Canis, Dipilidium with 1%, respectively. The percentage of prevalence is that the breed is mestizos with 18%, followed by the Pitbull breed with 5%, Husky 4%, French Poodle 4%, Pekingese 2%, Chihuahua with 2%, American Bully with 2 %, Dachshund 1%, Rotwailer with 1%, Beagle with 1% the rest with 60%. Regarding age, range from 1 to 3 months 25%, from 4 to 6 months 11%, from 7 to 9 months 3%, from 10 to 12 months 1% and without parasites 60%, considering that all puppies come from from homes that keep them as their pets and feed them balanced products related to their age and breed.